1980
DOI: 10.1007/bf01871169
|View full text |Cite
|
Sign up to set email alerts
|

Occluding junctions in a cultured transporting epithelium: Structural and functional heterogeneity

Abstract: MDCK cells (epithelioid of renal origin) form monolayers which are structurally and functionally similar to transporting epithelia. One of these similarities is the ability to form occluding junctions and act as permeability barriers. This article studies the junctions of MDCK monolayers formed on a permeable and transparent support (a disk of nylon cloth coated with collagen) by combining two different approaches: (i) Scanning of the electric field: the disk is mounted as a flat sheet between two Lucite chamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 54 publications
6
75
1
Order By: Relevance
“…Several aspects of our studies suggest that oxidants increased the permeability of this pathway. First, oxidants increased the transepithelial electrical conductance in an epithelium in which the predominant transepithelial conductive pathway is paracellular (10,12,13). Second, oxidants increased the permeability of the epithelium to mannitol, which predominately crosses the epithelium via an extracellular route (15,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several aspects of our studies suggest that oxidants increased the permeability of this pathway. First, oxidants increased the transepithelial electrical conductance in an epithelium in which the predominant transepithelial conductive pathway is paracellular (10,12,13). Second, oxidants increased the permeability of the epithelium to mannitol, which predominately crosses the epithelium via an extracellular route (15,18).…”
Section: Discussionmentioning
confidence: 99%
“…We chose the cultured renal epithelial cell line, Madin-Darby Canine Kidney (MDCK),' for this study, because: (a) its barrier function has been extensively characterized in our and other laboratories (10)(11)(12); (b) the cultured epithelium has an intact tight junction structure with a transepithelial electrical conductance (GJ) low enough to make measurements accurate and reproducible in a given monolayer, (c) the paracellular pathway is the predominant conductive pathway (10,12,13); (d) the study of a cultured epithelium eliminates the potential problem of participation of nonepithelial cells in any response; and (e) the epithelium is widely available and easily cultured.…”
Section: Introductionmentioning
confidence: 99%
“…This approach gave us an opportunity to study the development of the transporting epithelia phenotype. Thus we used it to study the synthesis, assembly, and sealing of tight junctions (TJs) (69,74,75,78,145,183,297), as well as the polarity of Na ϩ -K ϩ -ATPase (61,62,96,102); Enrique Rodriguez-Boulan introduced the use of viruses that bud either apically (e.g., Flu) or basolateraly (e.g., stomatitis) to track the fate of specific proteins during apical or basolateral polarity (283, 284, 379 -382), and Carlos A. Rabito analyzed the onset of polarized cotransporters (368,370,371). M. Taub perfected the approach by developing totally defined culture media (440 -442), and complementary procedures were refined to open and reseal the TJs by removing and restoring Ca 2ϩ (69,97,101,184,186), follow the cascades of phosphorylation involved (20,21,85), the role of the cytoskeleton (311, 312), the participation of protein synthesis and sorting (196,376,379,381), the polarized distribution of ion channels (317,359,360,361,421,439), the involvement of E-cadherin (199 -201), the effect of agents that induce differentiation (280), and the vectorial movement of receptors (302).…”
Section: Model Systems Of Transporting Epitheliamentioning
confidence: 99%
“…However, in vitro these cell lines do not exhibit a behaviour similar to that observed in a true epithelium. An epithelial cell line useful for studies on the parasite-cell interaction, such as those reported for Entamoeba histolytica (28) and Giardia lamblia (7), is the Madin-Darby canine kidney cell line (MDCK), whose electrical properties (5), morphology (29), metabolic aspects (6,18) and general behaviour on culture vessels (26), are well characterized.…”
mentioning
confidence: 99%